Process management and approaches in distance learning based on blended learning during the covid-19 pandemic - Hisam Ahyani; Syamsudin Syamsudin; Suharyanto H Soro; Naeli Mutmainah (Faculty of Education, Universitas Negeri Yogyakarta, 2022)
Today, especially during the covid-19 pandemic, as it is today, all activities of educational institutions or madrasas/schools must carry out the online learning process. One of the learning innovations that can be carried out by madrasas/schools is by implementing blended learning-based distance learning. This study aims to determine how management, learning planning, and evaluation of learning based on blended learning are carried out at MA Al Azhar, Banjar, Indonesia. The number of respondents in this study consisted of 15 teachers spread across various fields of study. The study used qualitative data analysis techniques with descriptive methods. As a result, research shows that at the planning stage, schools had previously formulated a special curriculum that was adapted to the blended learning model carried out during the covid-19 pandemic, this was also supported by very adequate learning facilities and infrastructure. At the implementation stage, there are differences in the use of the learning approach with real events in the field, namely the time shift in utilizing learning. MA Al Azhar applies a 50% system: 50% in the use of learning, a week of face-to-face learning and the following week is an online system. At the evaluation stage, MA Al Azhar carried out face-to-face and online-based evaluations such as the use of evaluations through recapitulation results on google classroom and excel on google classroom.